APPLICATION OF THE GGG PRINCIPLES IN THE PLANNING, IMPLEMENTATION,AND ACCOUNTABILITY ALLOCATION OF VILLAGE FUNDS: Study in Desa in Kecamatan Sunggal , Kabupaten Deli Serdang - Mesakh, Januardi; Simanjuntak, Arthur; Siahaan, Septony B.; Br. Sembiring, Vebina N. (Majalah Ilmiah METHODA, 2023)
This research aims toto know and examine the implementation of the principle Good Government Governance (Participation, Transparency, and Accountability) in Planning, Implementation, Accountability for Allocation of Village Funds to villages in Sunggal District, Deli Serdang Regency.The type of research used is causal associative using questionnaires and survey research methods. The approach used in this research is a quantitative approach. The location of the research was carried out in villages in Sunggal District while determining the number of respondents for each village in the form of: Kepala Desa (Kades), Seketaris Desa (Sekdes), Kaur Keuangan, Kasi Pemeritahan serta Lembaga Swadaya Masyarakat. Based on the results of research, partially principles Good Government Governance (Participation) and Good Government Governance (Accountability) has a positive and significant effect on Planning, and Accountability for Allocation of Village Funds, meanwhile Good Government Governance (Transparency) has a positive and insignificant effect on the Village Fund Allocation Implementation. Simultaneously principle Good Government Governance (Participation, Transparency, Accountability) has a positive and significant effect on the Planning, Implementation, and Accountability of Village Fund Allocations.